Toward quantifying capacity losses due to solid electrolyte interphase evolution in silicon thin film batteries - Steinrück, Hans-Georg; Cao, Chuntian; Veith, Gabriel M.; Toney, Michael F. (The Journal of Chemical Physics)

Structural Origins of Light-Induced Phase Segregation in Organic-Inorganic Halide Perovskite Photovoltaic Materials - Beal, Rachel E.; Hagström, Nanna Zhou; Barrier, Julien; Gold-Parker, Aryeh; Prasanna, Rohit; Bush, Kevin A.; Passarello, Donata; Schelhas, Laura T.; Brüning, Karsten; Tassone, Christopher J.; Steinrück, Hans-Georg; McGehee, Michael D.; et al. (Matter)

Shedding X-ray Light on the Interfacial Electrochemistry of Silicon Anodes for Li-Ion Batteries - Cao, Chuntian; Shyam, Badri; Wang, Jiajun; Toney, Michael F.; Steinrück, Hans-Georg (Accounts of Chemical Research)

Morphology of Organic Semiconductors Electrically Doped from Solution Using Phosphomolybdic Acid - Huang, Tzu-Yen; Larrain, Felipe A.; Borca, Carlos H.; Fuentes-Hernandez, Canek; Yan, Hongping; Schneider, Sebastian Alexander; Chou, Wen-Fang; Rodriguez-Toro, Victor A.; Steinrück, Hans-Georg; Cao, Chuntian; Sherrill, C. David; Kippelen, Bernard; et al. (Chemistry of Materials)

Solid Electrolyte Interphase on Native Oxide-Terminated Silicon Anodes for Li-Ion Batteries - Cao, Chuntian; Abate, Iwnetim Iwnetu; Sivonxay, Eric; Shyam, Badri; Jia, Chunjing; Moritz, Brian; Devereaux, Thomas P.; Persson, Kristin A.; Steinrück, Hans-Georg; Toney, Michael F. (Joule)

Novel ALD Chemistry Enabled Low-Temperature Synthesis of Lithium Fluoride Coatings for Durable Lithium Anodes - Chen, Lin; Chen, Kan-Sheng; Chen, Xinjie; Ramirez, Giovanni; Huang, Zhennan; Geise, Natalie R.; Steinrück, Hans-Georg; Fisher, Brandon L.; Shahbazian-Yassar, Reza; Toney, Michael F.; Hersam, Mark C.; Elam, Jeffrey W. (ACS Applied Materials & Interfaces)

Fluoroethylene Carbonate Induces Ordered Electrolyte Interface on Silicon and Sapphire Surfaces as Revealed by Sum Frequency Generation Vibrational Spectroscopy and X-ray Reflectivity - Horowitz, Yonatan; Steinrück, Hans-Georg; Han, Hui-Ling; Cao, Chuntian; Abate, Iwnetim Iwnetu; Tsao, Yuchi; Toney, Michael F.; Somorjai, Gabor A. (Nano Letters)

The nanoscale structure of the electrolyte–metal oxide interface - Steinrück, Hans-Georg; Cao, Chuntian; Tsao, Yuchi; Takacs, Christopher J.; Konovalov, Oleg; Vatamanu, Jenel; Borodin, Oleg; Toney, Michael F. (Energy & Environmental Science)
Combined experimental and theoretical insights into electrolyte–electrode interfaces relevant to lithium ion batteries.

Surface structure evolution in a homologous series of ionic liquids - Haddad, Julia; Pontoni, Diego; Murphy, Bridget M.; Festersen, Sven; Runge, Benjamin; Magnussen, Olaf M.; Steinrück, Hans-Georg; Reichert, Harald; Ocko, Benjamin M.; Deutsch, Moshe (Proceedings of the National Academy of Sciences)
Interfaces of room temperature ionic liquids (RTILs) are important for both applications and basic science and are therefore intensely studied. However, the evolution of their interface structure with the cation’s alkyl chain length n from Coulomb to van der Waals interaction domination has not yet been studied for even a single broad homologous RTIL series. We present here such a study of the liquid–air interface for n=2to 22 , using angstrom-resolution X-ray methods. For n<6 , a typical “simple liquid” monotonic surface-normal electron density profile ρe(z) is obtained, like those of water and organic solvents. For n>6 , increasingly more pronounced nanoscale self-segregation of the molecules’ charged moieties and apolar chains yields surface layering with alternating regions of headgroups and chains. The layering decays into the bulk over a few, to a few tens, of nanometers. The layering periods and decay lengths, their linear n dependence, and slopes are discussed within two models, one with partial-chain interdigitation and the other with liquid-like chains. No surface-parallel long-range order is found within the surface layer. For n=22 , a different surface phase is observed above melting. Our results also impact general liquid-phase issues like supramolecular self-aggregation and bulk–surface structure relations.

Effect of Structure and Disorder on the Charge Transport in Defined Self-Assembled Monolayers of Organic Semiconductors - Schmaltz, Thomas; Gothe, Bastian; Krause, Andreas; Leitherer, Susanne; Steinrück, Hans-Georg; Thoss, Michael; Clark, Timothy; Halik, Marcus (ACS Nano)

The Atomic Scale Electrochemical Lithiation and Delithiation Process of Silicon - Cao, Chuntian; Steinrück, Hans-Georg; Shyam, Badri; Toney, Michael F. (Advanced Materials Interfaces)

Memory Effect of Self-Assembled PS-b-PEO Block Copolymer Films with Selectively Embedded Functionalized TiO2 Nanoparticles - Kirschner, Johannes; Will, Johannes; Rejek, Tobias J.; Portilla, Luis; Berlinghof, Marvin; Schweizer, Peter; Spiecker, Erdmann; Steinrück, Hans-Georg; Unruh, Tobias; Halik, Marcus (Advanced Materials Interfaces)

Noble metal free photocatalytic H2 generation on black TiO2: On the influence of crystal facets vs. crystal damage - Liu, Ning; Steinrück, Hans-Georg; Osvet, Andres; Yang, Yuyun; Schmuki, Patrik (Applied Physics Letters)

Nanoscale Structure of the Oil-Water Interface - Fukuto, M.; Ocko, B. M.; Bonthuis, D. J.; Netz, R. R.; Steinrück, Hans-Georg; Pontoni, D.; Kuzmenko, I.; Haddad, J.; Deutsch, M. (Physical Review Letters)

In Situ Study of Silicon Electrode Lithiation with X-ray Reflectivity - Cao, Chuntian; Steinrück, Hans-Georg; Shyam, Badri; Stone, Kevin H.; Toney, Michael F. (Nano Letters)

Structure of n-Alkyltrichlorosilane Monolayers on Si(100)/SiO2 - Steinrück, Hans-Georg; Will, J.; Magerl, A.; Ocko, B. M. (Langmuir)

Order and Melting in Self-Assembled Alkanol Monolayers on Amorphous SiO2 - Haddad, Julia; Steinrück, Hans-Georg; Hlaing, Htay; Kewalramani, Sumit; Pontoni, Diego; Reichert, Harald; Murphy, Bridget M.; Festersen, Sven; Runge, Benjamin; Magnussen, Olaf M.; Magerl, Andreas; Deutsch, Moshe; et al. (The Journal of Physical Chemistry C)

Structural Investigations of Self-Assembled Monolayers for Organic Electronics: Results from X-ray Reflectivity - Khassanov, Artoem; Steinrück, Hans-Georg; Schmaltz, Thomas; Magerl, Andreas; Halik, Marcus (Accounts of Chemical Research)

In situ investigation of two-step nucleation and growth of CdS nanoparticles from solution - Schiener, A.; Magerl, A.; Krach, A.; Seifert, S.; Steinrück, Hans-Georg; Zagorac, J.; Zahn, D.; Weihrich, R. (Nanoscale)

Nanoscale Structure of Si/SiO2/Organics Interfaces - Steinrück, Hans-Georg; Schiener, Andreas; Schindler, Torben; Will, Johannes; Magerl, Andreas; Konovalov, Oleg; Li Destri, Giovanni; Seeck, Oliver H.; Mezger, Markus; Haddad, Julia; Deutsch, Moshe; Checco, Antonio; et al. (ACS Nano)